The side-out complex in volleyball: the effect of reception and attack performance with the final score. - Lobietti, R.; Cabrini, P.; Brunetti, M. (World Congress of Performance Analysis of Sport VIII, 2008)
Statistical analyses for each category allowed to identify the limit index between victory and defeat. The method used in this study, classifying in six categories the type of results, permitted to identify different target for players and coaches. The evaluation of passing confirmed the importance to avoid passing errors. At the level we analysed (B1 Male Italian League) coaches and players receive from this study some target to remind and to try to reach in practice and in matches: · Passing error showed significant difference: when passing errors are over the 5% the possibility to lose is very high and over 7% the difference in the final score becomes higher than 3 points. · Attack points under 51% and attack errors over 10% predict a defeat; when attack points are over the 58% and attack blocked under the 7% the possibilities to win are very high. · After perfect passes, more than 31% of kills and less than 2.5% spike stuffed could be enough to win; instead, after a bad pass attack errors and undergoing blocks over the 5% conduct to a defeat. · The deeper analysis conducted by means of the Kruskal Wallis confirmed the importance of the setter`s efficiency (Papadimitriou et al. 2004) especially when the pass are perfect and good. Further studies will be conducted analysing games at different level to see if the parameters that differentiate the type of score will result the same.